Manga versus webtoon: Alternative science learning module based on Dr Stone - Kiki Septaria; Atika Fatharani (Jurnal Inovasi Pendidikan IPA, 2022)
Reading activities for junior high school students in Indonesia are carried out at school when the instructor requests that they study the learning topic being taught. Therefore, learners may become bored due to the thickness of the available books. Indonesian students are more likely to read when they encounter visualizations in images, and a small amount of text, commonly referred to as comics. Students like reading numerous popular comics, such as manga and webtoons, but it is exceptionally uncommon to discover a popular comic that teaches the subject of a specific discipline, particularly natural sciences, which has a challenging scientific picture. This study aims to examine the many forms of manga comics and webtoons that may be utilized as alternative student learning modules when students study from home without regard for space or time constraints during the covid-19 epidemic. The descriptive qualitative research approach was applied. Manga comics, particularly Dr Stone's manga, were more acceptable for use as alternative scientific learning modules in junior high schools in terms of completeness of module parts and learning contexts. Comic Dr Stone can boost learners' cognitive and psychomotor skills by vividly seeing daily situations. This research is intended to be expanded by further researchers to give more alternative module alternatives for students and aid teachers in educating Indonesian learners.